Craft brewery HACCP: prerequisite programs based on good manufacturing practices developed for Boulevard Brewing Company, Kansas City, MO. - Baughman, Neal R. (Kansas State University, 2015)
The brewing industry has, historically, had little food safety regulation. In response to the September 11th attacks, new legislation culminating in the Food Safety Modernization Act of 2010 was established and reinforced food safety regulations for the brewing industry. Under this expanded regulation, breweries are required to comply with the modernized Current Good Manufacturing Practices (cGMPs). The regulatory climate for the brewing industry is very complicated. The brewing industry is regulated primarily under the jurisdiction of the Alcohol and Tobacco Tax and Trade Bureau and the Food and Drug Administration. Based upon the regulatory environment and business considerations, Boulevard Brewing Company has opted to develop a Hazard Analysis and Critical Control Point (HACCP) plan. Before a HACCP plan can be implemented a foundation of prerequisite programs, based on the FDA’s cGMPs, must be in place. Prerequisite programs establish the operational and environmental conditions required for a successful HACCP plan. Failure to comply with the cGMPs can lead to fines, re‐inspection fees, forced recalls, and possible criminal prosecution. Prerequisite programs were developed for the following areas: facilities, including sanitary design principles, utilities, traffic and product flow; production equipment, including preventive maintenance and calibration; receiving, warehousing, and shipping, including supplier control, chemical control, and raw material testing; pest control for insects, rodents and birds; cleaning and sanitation under a Master Sanitation Schedule; specifications, including ingredients, products, and packaging materials; personal hygiene for both employees and visitors; and lastly a system of traceability and recall. These prerequisite programs, based on cGMPs, are required to ensure regulatory compliance while minimizing regulatory and fiscal risks.
Keywords: HACCP; Prerequisite; cGMP; Brewery; Boulevard; Beer; Food Science (0359)